Ageing, osteoporosis, and intellectual disability; risks differ, and diagnosis can be missed - Burke, Eilish; Mc Carron, Mary; O'Dwyer, Maire (My University, 2024)
Background: People with intellectual disability often present atypically for various health conditions, making it challenging to identify concerns, particularly when communication challenges are also considered. Additionally, they may face barriers to healthcare access, resulting in many conditions going unnoticed. Health screening inequities are also evident in this population, and osteoporosis, a silent condition often only diagnosed postfracture, requires screening; however, if this does not happen, it may result in unnecessary fracture. Therefore the aim of this study is to identify predictors of osteoporosis in older adults with intellectual disability and examine potential inequity in the diagnosis of the condition. Methods: The study used data from the Intellectual Disability Supplement to The Irish Longitudinal Study on Ageing (IDS‐TILDA). Bone quality was measured using quantitative ultrasound (QUS). Logistic regression was performed to identify significant predictors of poor bone quality, including chronic health conditions, dietary intake, medication use and activity levels. Results: Out of 575 participants who completed QUS, osteoporosis prevalence was objectively measured at 41%, with a further 33.2% measured within the osteopenic range, but less than 2 in 10 had a doctor's diagnosis of osteoporosis. Reported Dual‐Energy X‐ray Absorptiometry screening uptake was low at 18.2%. Three major predictor variables of osteoporosis and osteopenia were found significant: difficulty walking 100 yards, taking antiepileptic drugs medicines and taking proton pump inhibitors. The model achieved an overall classification accuracy of 70.8% for osteopenia and 72.5% for identifying osteoporosis. Conclusion: The study highlights the different risk factors in people with intellectual disability, the potential for missed diagnoses and the likelihood there is inadequate screening. There is an urgent need for robust risk assessment and reasonable adjustments to ensure equitable screening and targeted preventive strategies. Clinicians must consider specific concerns for this population to avoid missed diagnoses and reduce the adverse effects of osteoporosis/osteopenia, such as an increased risk of fragility fractures.
ACCEPTED
Keywords: assessment inequalities; intellectual disability; osteoporosis; risk factors; Ageing; Bone health; Intellectual Disability; OSTEOPOROSIS; RISK FACTORS; health inequalities; Chronic Health Condition; Intellectual Disability; Accessibility; Health